Analysis of the Rasch Model: Validity of Students' Mathematical Creative Thinking Ability on Quadratic Function Material - Yusfiah, Khaerani; Zakiyah, Siti; Faradillah, Ayu; Jusra, Hella (Pattimura Proceeding, 2024)
Creative thinking skills are important skills in the world of education, but students are less enthusiastic when solving math problems which causes students' mathematical creative thinking skills to be low. This study aims to determine the validity of students' mathematical creative thinking skills on quadratic function material with the Rasch Model. This study uses a quantitative method with a survey approach. The subjects of this study are 106 students consisting of school students, this research is carried out by testing instruments on research subjects. Through the instrument, there are four indicators consisting of eight questions that are tested for validity and bias using the Rasch Model, the results are that all items are declared fit on the validity test, 24 people are declared misfit, with a reliability test score of 0.73 including high criteria and seven items are indicated as biased items.